Polyurethane nanofibers coatings on the x-ray film by using electrospinning techniques - Nurul Nadirah, Suteris (2017)
This thesis is about synthesizing polyurethane (PU) solution. The purpose of conducting this research are to prepare a polymer nanofibers using electrospinning technique. Electrospinning is the technique of nanofabrication of polymer nanofibers. The synthesization of the solution is dissolved in N,N-dimethylformamide (DMF) with 12 wt.% and the solutions is mixed using magnetic stirrer. After that, the polyurethane nanofibers was obtained by using electrospinning machine with a voltage of 30kV, a flow range of 1.00 ml/h and working distance of 8 cm. The results demonstrated that the SEM images is more clearer as the magnification increases. Attenuated total reflection – fourier transform infrares (ATR-FTIR) shows that the PU electrospun has maintained it’s molecular structure during the electrospinning process. The spinnable parameters are very important in this research to ensure that the polyurethane can be coated properly on the X-ray film.